Komercializacija, kapitalizem in praznovanje - Santino, Jack (Traditiones, 2005)
<span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Traditional holidays in the United States have become remarkable for the amount of commercial activity (Christmas, Halloween). When it is recognized that rituals, festivals, and celebrations are often dramatic symbolic enactments of the culture that produced them, one realizes that it is inevitable that such a class of events would exist. Often the commercialization of holidays starts with the recognition of traditional customs and activities customs are recognized as potentially profitable and exploitable by various industrial interests, and are commercialized as a result. Another, somewhat different, process involves the attempt to translate a custom or a practice associated with a particular holiday to a different festival. The third process focuses on the translations of festive year into mass media (music, film, literature) where one obvious dynamic in the commercialization of a holiday is the fit between the holiday and the genre in question. What is ultimately most interesting is how people actually use the mass media and commercial goods. People continue to adapt their customs and traditions and create new ones; they use the products of mass culture to create meaning within the contexts of their own priorities and their own lives. Celebrations require personal interaction, and it is within the realm of interpersonal communication that real social bonds are created and maintained. <span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">*** <span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Tradicionalni prazniki v ZDA so izjemni po vseobsežni komercializaciji (najbolj božič, nato noč čarovnic). Ker so rituali, festivali in praznovanja pogosto dramatične simbolične uprizoritve kulture, katere produkt so, je neogibno, da so tudi del porabniške kulture. Avtor komercializacijo opazuje na več na več ravneh: pogosto se začne z ugotovitvijo, da so tradicionalne šege in aktivnosti vnovčljive: komercializaciji je podvržen ves kontekst enega samega praznika (industrija poskrbi za vso tradicionalno praznično opravo); nekoliko drugačen proces je poskus prenosa značilnosti enega praznika na druge; tretji pa je prevajane prazničnega leta v množične medije (literatura, glasba, film), pri čemer dinamika komercializacije temelji na ujemanju praznika in žanra. Najzanimivejše pa je, kako ljudje uporabljajo medije in komercialne produkte. Prilagajajo si šege in izročila in ustvarjajo nova, uporabljajo množične produkte, da si osmišljajo svoje želje in življenje. Praznovanj ni brez osebnih stikov in prave socialne vezi se ustvarjajo in vzdržujejo le z medčloveškimi stiki in komunikacijo.